FINANCIAL DISTRESS ANALYSIS OF INDONESIA RETAIL COMPANIES - Yulian, Yelli (Lembaga Penerbitan Unversitas Esa Unggul, 2020)
The retail industry is basically an industry whose business activities provide products in the form of goods and or services. In 2016 the development of global retail recorded that Indonesia entered the top five countries most active retail as well as the top five countries with the largest sales in Asia. In the past few years there have been many closures of retail outlets in Indonesia. The current condition of retail in Indonesia faces many problems, one of which is the distortion of new income, that is, retail that has no place or is usually called electronic commerce (e-commerce). E-commerce involves the purchase and sale of products (such as physical goods, digital products or services) transacted over computer networks. This study uses the data from 23 companies retail business in Indonesia and data collected from 2013 to 2017. Analyzed using data panel regression with three approaches Altman, Springate and Zmijewski. All companies experienced a decline in financial performance. The factors that influence the condition of financial distress are the net profit margin, current ratio, size of firm and total asset turnover.